Faktor yang Berhubungan dengan Upaya Penanganan Keluhan Dismenore pada Siswi SMK Negeri 17 Samarinda - Paiya Padang Herlina; Risva; Tanti Asrianti (Fakultas Kesehatan Masyarakat Universitas Dayanu Ikhsanuddin, 2022)
Dysmenorrhea are still quite high but there are still few young women who seek information about dysmenorrhea and the impact it causes. This triggers young women to pay less attention to the handling efforts made when experiencing complaints of menstrual pain. This study aims to find out the relationship between knowledge, the degree of pain and exposure to information with efforts to handle dysmenorrhea complaints. This type of research is quantitative with a cross sectional approach. The study population was 425 with a sample of 197 people using purposive sampling techniques. The data was taken using questionnaires. Analysis of the data used using the Spearman Rank Test with a 95% confidence level. The results showed that respondents' handling efforts were in the good category (39.6%), respondents' knowledge levels were in the good category (58.4%), respondents' pain levels were in the category of mild pain (58.9%) and the respondent information exposure category was in the exposure category (61.9%). The study's conclusions showed there was a relationship between knowledge (p-value 0.000), degree of pain (p-value 0.035) and exposure to information (p-value 0.049) with efforts to handle dismenore complaints. It is recommended to be able to increase socialization evenly to all students so that each student gets the same information in addition to it is recommended that students can improve handling such as exercising, doing knee chest positions and doing examinations to the doctor and maximizing parental support as an accurate source of information